Management of periodontally compromised mandibular molar with Hemisectioning: A case report - Bandu Napte; Srinidhi Surya Raghavendra (Wolters Kluwer Medknow Publications, 2014)
Introduction: Hemisection involves sectioning of a periodontally involved mandibular molar so as to remove the involved root and save the remaining tooth. This procedure helps in saving a tooth which otherwise would have been deemed for extraction. Hemisection refers to removal or separation of root with its accompanying crown portion of two-rooted teeth, most commonly mandibular molars. Method: In this case report, an advanced Endo-Perio lesion on a left mandibular first molar was successfully treated by root-canal treatment and hemisection. This procedure helps preserve the tooth structure, alveolar bone and promote cost savings over other treatment options. Conclusion: Hemisection is a treatment option for saving a mandibular molar which is in advanced stage of periodontal disease of one root. Removal of the affected root will help in retaining the remaining tooth structure.